Pemilihan Kepala Daerah Jalur Independen dalam Ketatanegaraan Indonesia: Studi Kasus Kota Baubau Tahun 2025 - zubair zubair (Jurnal Hukum Lex Generalis, 2025)
This study examines the position of independent candidates within the Indonesian constitutional system, as well as the opportunities and challenges they face in regional head elections, focusing on the 2018 Baubau City election. Since the Constitutional Court Decision No. 5/PUU-V/2007, independent candidates have obtained legal legitimacy to run without going through political parties. However, stringent administrative requirements—such as collecting support from at least 10% of registered voters (DPT) and ensuring support is spread across more than 50% of sub-districts—pose significant challenges. Independent candidates have opportunities through direct engagement with the community, freedom from political levies, and public dissatisfaction with political parties. Nevertheless, they also face obstacles such as limited resources, the absence of political machinery, and discrepancies between initial support and actual votes. This study concludes that fairer regulations and systemic support are necessary to strengthen the existence of independent candidates in local democracy.